Trading Refugees: The Governance of Refugee Settlement in a Decentralized Welfare State. (18th February 2020) - Askim, Jostein; Steen, Anton
Abstract : In a decentralized welfare state, central and local governments need each other to settle refugees. Using the case of Norway, the article studies how these interdependencies have been governed over time, including through the 2015–2016 refugee crisis. Norway's refugee settlement programme is a conscious hybrid of market and network governance and it has remained essentially stable for more than 20 years, despite several changes in government, large fluctuations in the number of refugees, and long periods of poor performance vis‐à‐vis settlement targets. This surprising programme stability is explained by a combination of extraordinary political adherence to the democratic value of local government autonomy, the cupidity of local governments, and abundant state economic resources during the period under study.